PENGARUH PENDIDIKAN DAN PEKERJAAN TERHADAP PEMBERIAN AIR SUSU IBU EKSLUSIF - Ni Made Rosiyana; Enggar Enggar; Yuni Kristiani Tumani (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2022)
Breast milk is the best food for babies in the first 0-6 months of life. The nutritional needs of protein, carbohydrates, fats, vitamins and minerals can all be fulfilled from breast milk. Exclusive breastfeeding is influenced by many factors including work and education. This study aims to determine the effect of work and education on exclusive breastfeeding at the Bulili Health Center, Palu City. This research is a descriptive correlative research with a cross sectional approach. The population in this study were all mothers who had babies aged 6-24 months in the working area of ​​the Bulili Health Center. The sample of this research is 150 people, the sampling technique is purposive sampling technique. The analysis used in this research is univariate and crosstab analysis. The results showed that of the 150 respondents, judging from the occupation, 57.3% of working and non-working mothers/IRT 42.7%, (p= 0.826). When viewed from the education factor, it was found that 34.7% had basic education, 30.7% had secondary education and 34.7% had higher education (p: 0.555). The conclusion from the results of this study is that there is no effect of work and education on exclusive breastfeeding at the Bulili Health Center, Palu City.